CERVICAL TETRAPARESIS CAUSED BY HERNIATED DISCS: A CASE REPORT - Djunadi, Joshua; Suryo, Martin Firman (INFOKUM, 2022)
Tetraparesis means weakness of muscle strength in all four extremities. Tetraparesis is one of the most common symptoms in daily practice but is often treated in a less comprehensive manner without finding out the root cause of the problem causing increased progression and worsening the prognosis of the disease. We report a case of cervical tetraparesis due to disc herniated in a 63-year-old woman with complaints of cramping in both hands for 10 months ago and lower back pain. Complaints such as tingling, fever, night pain, unexplained weight loss, nausea, and vomiting were denied. On physical examination, there was a decrease in motor strength in all four limbs, an increase in physiological reflexes, pathological reflexes positive, and decrease in sensory function. Cervical MRI examination revealed cervical spondylosis with degenerative discs. HNP Central discs C2 to C3, C4 to C5, and C5 to C6 pressing heavily on the thecal sac, no neural foramen narrowing was seen. Protrusion of C3 to C4 and C6 to C7 centers compressing the thecal sac and neural foramen bilaterally, suggestive of compression irritating to bilateral C3 and C6 roots. The treatment given was laminectomy surgery with pedicle fixation and pharmacologic such as Methylprednisolone 4 x 125 mg, Omeprazole 2 x 20 mg, Tizanidine 1 x 2 grams, Provlyn 3 x 50 mg, and Ketorolac tromethamine 3 x 10 mg with good results without any complication. The patient's prognosis is good.